Inovasi Kuliner RiceBowl Udang Krispy Saus Pedas Manis sebagai Peluang Usaha di Kelurahan Lingkas Ujung - Nurul Hidayat; Anisah Nurfahmi; Herwin Herwin; Intan Feiduri; Lianti Lianti; Muhamad Akil Saputra; Nur Syarifah Athira (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This study aims to examine the potential for developing culinary businesses based on innovation, especially ricebowls with crispy shrimp with sweet and spicy sauce, as a business opportunity in Lingkas Ujung Village. ricebowls with crispy shrimp with sweet and spicy sauce are a food innovation that combines spicy, sweet and crispy flavors, which can attract consumers, especially children, students and workers. The manufacturing process begins with the selection of quality raw materials, followed by the right shrimp processing techniques to produce an optimal crispy texture. The sweet and spicy sauce is designed to provide an attractive balance of spicy and sweet flavors. This study was also conducted in Lingkas Ujung Village to determine public interest in the product. The results of the study indicate that there is a large market potential in this area, with a positive response from consumers who have tasted the product. In addition, financial analysis shows that this culinary business has profitable prospects with reasonable capital and profit calculations. Thus, the culinary innovation of ricebowls with crispy shrimp with sweet and spicy sauce can be a promising business opportunity and has the potential to develop in Lingkas Ujung Village.